Pemberdayaan Guru Raudhatul Athfal (RA) Melalui Edukasi Media Visual “Buku Bantal Bilingual” di Sukosono Kedung Jepara Jawa Tengah - Santi Andriyani; Yushinta Eka Farida; DS. Drajat Wibowo (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2018)
Media has an important role in the learning process of early childhood. Media can be used as a tool to facilitate learning process to be effective and eficient. This program is done at Raudhatul Athfal (RA) Al- Masithoh and Raudhatul Athfal Miftahul Ulum, both are located in Sukosono, Kedung, Jepara. The objectives of this program are: (1) to develop the creativity of RA teachers on creating instructional media; (2) to increase the knowledge and skills of RA teachers on learning media, called softbook; (3) to improve the linguistic intelligence of students using bilingual softbook as a learning medium. The methods used are education, training, education, and practice. The results of this program are: (1) the output or product in this program is a softbook (buku bantal) made from spons ati as the basic material. It is related to RA theme with bilingual concept (Indonesian and English) and (2) schools could practice of making the bilingual softbook according to the stages started from drawing, painting, writing, sticking, decorating , sewing, and the last is finishing.